2021
DOI: 10.3389/fpubh.2021.653884
|View full text |Cite
|
Sign up to set email alerts
|

To the Operating Room! Positive Effects of a Healthcare Clown Intervention on Children Undergoing Surgery

Abstract: In the present study we examined the positive effects of a healthcare clown intervention on children undergoing surgeries, and the role parent-child relationships may play in their effectiveness. Children between 5 and 12 years, who were scheduled to undergo elective surgical procedures in a large university hospital, were randomly assigned to an intervention group (IG; n = 35) that was visited by a healthcare clown, and a control group (CG; n = 27) that received treatment as usual (i.e., company of parents be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 71 publications
0
6
0
4
Order By: Relevance
“…Whereas regarding work with children, greater importance is given to the emotional impact and the empathic resonance of the setting (for both operators and children), the operator’s dynamic and creative ability to engage and defocus the children, thus triggering positive emotions, imagination, and identification in them, demonstrating at the same time excellent coping skills and personal resilience, nourished by confidence in the human and social value of the work carried out. With regard to the benefits of professional clowning with children having problems of varying severity, recurrent and congruent indications can be found in recent literature [ 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 92%
“…Whereas regarding work with children, greater importance is given to the emotional impact and the empathic resonance of the setting (for both operators and children), the operator’s dynamic and creative ability to engage and defocus the children, thus triggering positive emotions, imagination, and identification in them, demonstrating at the same time excellent coping skills and personal resilience, nourished by confidence in the human and social value of the work carried out. With regard to the benefits of professional clowning with children having problems of varying severity, recurrent and congruent indications can be found in recent literature [ 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 92%
“…When we look at the studies on the use of laughter and humor in therapy, we can see that the use of laughter and humor in reducing stress and anxiety (Hae Jeong et al 2011, Ensook and Yeon Hee 2012, Kim et al 2015, Yim 2016, Friedler et al 2017, Memarian et al, 2017, Markova et al 2021, Meier et al 2021, which is the most important issue in the region. In terms of reducing the stress of sick individuals, dialysis patients (Bennet et al 2014), women undergoing in vitro fertilization treatment (Friedler et al 2017) studies were conducted.…”
Section: Studies On the Use Of Humor In Therapymentioning
confidence: 99%
“…It has also been observed that the use of clowning therapeutically during venous blood sampling has positive effects on pain and anxiety (Meiri et al 2016, Kurudirek et al 2021. The use of clowns in hospitals has been shown to reduce not only the anxiety of children and adolescents but also that of their parents (Agostini et al 2014;Markova et al 2021). Regarding anxiety reduction, Markova et al (2021) with children between the ages of 5 and 12, the positive effects of a health worker dressed as a clown on reducing anxiety in children undergoing surgery and how parent-child relationships play a role in their effectiveness were examined.…”
Section: Studies On the Use Of Humor In Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare clowning aims at addressing these issues by offering individual attention to patients in need, switching focus away from negative emotions to humorous play, and valuing a patient's unique strengths in an otherwise possibly impersonal environment. These encounters lead to improved communication, attention, energy, and mood [13]. Moreover, healthcare clowning has been conceptualized as a model for a more self-compassionate way of dealing with one's own shortcomings and hardships [14].…”
Section: Introductionmentioning
confidence: 99%